Sistem Pendukung Keputusan Menentukan Lokasi Tanam Tanaman Holtikultura ( Sayuran ) Menggunakan Metode Topsis - Suyatmo, Suyatmo; , Aris Rakhmadi, S.T., M. Eng (2017)
Indonesia is a potential country, the most fluenced potency is in the agricultural sector. As an agriculture country that has many island and mountain, it has the various plants. It caused by the temperature, soil PH, soil condition and water sources. To improve the production and agriculture quality should be researched and right decision. The research use TOPSIS method (Technique Order Preference by Similarity to Ideal Solution). TOPSIS is based on the concept which the best alternative will be choosen, and not only has the shortest distance from the positive ideal solution, but also has the longest from the negative ideal solution. Decision making determines embed this land with the criteria inside. That criteria based on the terms of the growing plant are height, temperature, soil Ph, soil conditions and water sources. A questionnaire were applied in order to get the results and find out how large the benefits of the system. The design of the application was created using programming languages such as PHP, MySQL, and the MySQL database CI. Based on the research results, it can be concluded that the existence of such a system can help the farmer groups in determining the location of the land with the support of detailed questionnaire results acquisition of 66,07%.